Is Gen Z So Different? An Analysis of the Impact of Comparative Advertising - Gajanová, Ľubica; Nadányiová, Margaréta; Majerová, Jana; Kollár, Boris; Pražáková, Anna (Communication Today, 2023)
Comparative advertising, the legislative regulation of which has long discouraged European companies from using it, has become an essential component of promotion in recent decades, although the approach of individual countries to it differs significantly and its influence varies depending on the cultural aspect, or the age of the recipients. The study deals with Generation Z, which differs from previous generations in general, and therefore it is not possible to use the same procedures and methods for them as for the rest of the population. The aim of the study was to find out whether comparative advertising is suitable for Generation Z as an extraordinary cohort and whether this segment of potential customers can be considered as a homogeneous group or a heterogeneous object for business marketing communication. It was determined whether Generation Z trusts this type of advertisement (ad believability) and whether this advertisement positively affects their purchase behaviour (purchase intention). Due to the nature of the research objectives, one-dimensional descriptive statistics and two-dimensional descriptive statistics for the evaluation of interdependent variables (Chi-square test) were used. Based on our research, it can be argued that Generation Z perceives comparative advertising differently from the rest of the population and cannot be subjected to the same processes as other generations.